Child of the dream : a memoir of 1963 - Robinson, Sharon, 1950- (Scholastic Inc., 2020)
Sharon Robinson, the daughter of baseball legend Jackie Robinson, reflects on her unique coming of age during the civil rights movement of 1963. While on the front lines of the struggle as her father's daughter, and helping host gatherings and fundraisers for notable civil rights dignitaries such as Martin Luther King Jr., thirteen-year-old Sharon also struggled with all the challenges of puberty as well as being one of the only black children in her wealthy neighborhood, and the pressures that accompany such a role.